PENGARUH ENKAPSULASI BENIH CABAI RAWIT (Capsicum frutescens L.) DENGAN BERBAGAI BAHAN PEMBAWA PADA BAHAN AKTIF Trichoderma spp. UNTUK PENGENDALIAN PENYAKIT LAYU FUSARIUM - Hidayat, Taufik; Nirwanto, Herry; Wuryandari, Yenny (JURNAL AGROTROPIKA, 2025)
Fusarium wilt is an important disease of cayenne pepper plants caused by the fungus Fusarium. Trichoderma is a type of biological agent that can be used to control plant diseases, one of which is fusarium wilt. This research was conducted to determine the effect of seed encapsulation with different carrier materials and the active ingredient Trichoderma in controlling fusarium wilt disease. This research was carried out in September 2023-January 2024, at the Plant Health Laboratory and Green House of UPN "Veteran" East Java. This research was prepared using a Completely Randomized Design (CRD) using 7 treatments and 3 replications. The data obtained were analyzed using analysis of variance with a further 5% DMRT test. The research results showed that the use of carrier materials and active ingredients of Trichoderma  influence on ability to control the fusarium wilt of cayenne pepper plants. The resulting inhibitory ability is categorized as capable of controlling fusarium wilt disease with an inhibitory ability of >50% (In vitro) and in vivo can reduce the intensity of the attack to <40%. Carrier materials glutinous flour (in vitro) and compost (in vivo) with the active ingredient Trichoderma harzianum are the best carrier materials in controlling fusarium wilt disease in cayenne pepper plants.